Vitreous Humour Extrusion after Suxamethonium Induction of Anaesthesia in a Polytraumatized Patient: A Case Report - Frederick Ebegue Amadasun; Theodore Ojeide Isesele (Case Reports in Medicine)
Introduction. Suxamethonium, a deepolarizing muscle relaxant, increases intraocular pressure. It is therefore advised to be avoided in open globe surgery, for fear of extruding ocular contents. Several anecdotal reports support this fear. Some workers however, dispute this claim. There is as yet no formal case report in the literature on the subject. Case Presentation. A 34-year old Nigerian male, was involved in a road traffic accident. He presented at the Accident & Emergency Unit of our hospital about 2 hours after the accident. Clinical examination revealed right corneal laceration (with intact ocular contents) and intra-abdominal visceral injury. Emergency laparotomy was scheduled, to be followed with corneal repair. Anaesthesia was induced with 10 mg midazolam, 100 mg ketamine, and 100 mg suxamethonium given intravenously in sequence. After laparotomy, the ophthalmologists reported for the corneal repair, only to find that the vitreous humour has been extruded. Conclusion. The fear about the use of suxamethonium in open globe situations is real. It will be good clinical judgment to use alternative drugs and techniques to effect rapid muscle relaxation, in the anaesthetic management of the open globe patient. This would be of interest to anaesthetists, ophthalmologists and clinical pharmacologists among others.